RESPUBLIKAMÍZDÍŃ ARQA ZONASÍN SUW MENEN TÁMIYINLEWDE «DOSLÍQ» KANALÍNÍŃ ÁHMIYETI - Nazarbekov, Q.K.; Allamuratov, K. (ILIM hám JÁMIYET, 2017)
The article is devoted to the works which are necessary to do in order to provide the state of water passing capacity of the “Dustlik” channel, the importance of water supply of the south regions of this channel and works done for many years on the territory of the republic.